Combined Balanced Magnetron Sputtering and Substrate-Annealing Synthesis for Pt and Pt/C Oxygen Reduction Catalysts. Issue 5 (22nd January 2016) - Sievers, Gustav; Quade, Antje; Kruth, Angela; Brüser, Volker
Abstract : The objective of this work is to enhance the understanding of magnetron-sputtered electrocatalytic films as a technological approach for proton exchange membrane fuel cell catalyst development especially with Pt and Pt/C sputtered layers on glassy carbon electrodes and gas diffusion electrodes. We have developed a dual-magnetron process for the deposition of Pt catalyst and a graphitic C catalyst support onto glassy carbon at elevated substrate temperatures. We characterized the different layers by XRD, XPS, SEM, cyclic voltammetry and linear sweep voltammetry. The electrocatalytic activity of Pt and Pt/C sputtered layers for the oxygen reduction reaction was found to be enhanced at higher temperatures. It was possible to synthesize carbon layers with slight graphitic characteristics as Pt support. Comparisons of the electrochemical properties of Pt and Pt/C sputtered layers showed a higher oxygen reduction activity for Pt deposited directly onto glassy carbon. However, the Pt structure was also observed to be significantly influenced by temperature, agglomeration occured. Pt deposition onto the graphitic carbon support on the other hand resulted in deposition of small Pt crystals, which were also stable at high temperatures. The catalyst structure before and after electrochemical testing indicates an increased stability at higher substrate temperatures during deposition and more crystal-like Pt assemblies versus an higher Pt mobility with particle-like Pt assemblies deposited at room temperature.